A nanoparticle priming agent reduces cellular uptake of cell-free DNA and enhances the sensitivity of liquid biopsies - Martin-Alonso, Carmen; Tabrizi, Shervin; Xiong, Kan; Blewett, Timothy; Patel, Sahil; An, Zhenyi; Sridhar, Sainetra; Bekdemir, Ahmet; Shea, Douglas; Amini, Ava; Wang, Shih-Ting; Kirkpatrick, Jesse; et al. (bioRxiv, 2023)
Liquid biopsies are enabling minimally invasive monitoring and molecular profiling of diseases across medicine, but their sensitivity remains limited by the scarcity of cell-free DNA (cfDNA) in blood. Here, we report an intravenous priming agent that is given prior to a blood draw to increase the abundance of cfDNA in circulation. Our priming agent consists of nanoparticles that act on the cells responsible for cfDNA clearance to slow down cfDNA uptake. In tumor-bearing mice, this agent increases the recovery of circulating tumor DNA (ctDNA) by up to 60-fold and improves the sensitivity of a ctDNA diagnostic assay from 0% to 75% at low tumor burden. We envision that this priming approach will significantly improve the performance of liquid biopsies across a wide range of clinical applications in oncology and beyond.